A major research project on Late Medieval and Early Renaissance music (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
This paper describes an important multimedia online project, dedicated to a number of different sources concerning Late Medieval and Early Renaissance music. The project, created by the University of Vienna, is continuously fostered by scholars all over Europe.DOI 10.17464/9788867742783
Keywords: Music; Renaissance; Habsburg; Austrian region